Study of Some Surfactants on Tin and Tin-Bismuth Electrodeposition from An Acid Electrolyte Sn(II) Sulphate - Rehamnia, Rabah; Messalhi, Abdelrani; Bensalem, Rachid; Chater, Rabah; Amirat, Samia; Chouchane, Sabiha (Asian Journal of Chemistry, 2010)
The effects of surfactants on the electrodeposition of tin and its alloy are studied. It appears that they provide several functions in the electrodeposition baths. They reduce the surface tension, strongly inhibit the process of metallic ions electroreduction, ensure the role of dispersants of poorly soluble brightening and improve the chemical stability of the electrolytes. These results have enabled us to choose the Syntanol DS-10 which added in small quantities: 2.5-10.0 g/L ensures a better functioning of the tinning bath. This product has an alkylic hydrocarbon chain, therefore biologically degradable. This is most important on the pollution point of view.